THERMODYNAMICS OF ADSORPTION OF DYES FROM AQUEOUS MEDIA ON ACTIVATED CHARCOAL - Iqbal, Muhammad Javed; Ashiq, Muhammad Naeem (Journal of Research (Science), 2007)
alizarin red-S, methyl blue, methylene blue, eriochrome black-T, malachite green, phenol red and methyl violet from aqueous media on activated charcoal has been investigated. The effect of shaking time and temperature on the adsorption behavior of these dyes has been studied. It was noted that adsorption of all the dyes on activated charcoal decrease with an increase in temperature. The adsorption isotherms at different temperatures were found to be of L-type. The thermodynamic parameters such as ΔG, ΔH and ΔS were calculated from the slopes and intercepts of the linear variation of lnK against 1/T, where K is the adsorption coefficient obtained from Langmuir equations was used. The calculated values for the heat of adsorption and the free energy indicate that adsorption process is favored at low temperatures.